Warriors of Imperial Japan in World War II 1941-45 (2601-05) - Antonucci, Claudio; Forniti, Renzo (Hong Kong : Concord Publication, 2010)
In terms of books dedicated to Axis forces during WWII, Germany consumes more than the lion's share of literature. Alas, there is little devoted to the fascinating subject of the Japanese soldier during this global conflict.
Keywords: Japan. -- Rikugun -- History -- World War, 1939-1945; Japan -- Rikugun -- Uniforms; Japan. -- Rikugun -- Equipment and supplies; World War, 1939-1945 -- Campaigns; Soldados japoneses